China Economic Update, December 2019 : Cyclical Risks and Structural Imperatives - World Bank Group (World Bank, Washington, DC, 2019)
China's economy is slowing, reflecting cyclical factors and longer-term structural trends. Notwithstanding the recent conclusion of the phase one agreement between China and the United States, short-term risks remain tilted to the downside amid a fragile global outlook and the lingering impact of trade tensions, especially on confidence. Adverse demographics, tepid productivity growth, and the legacies of excessive borrowing and environmental pollution will continue to weigh on growth over the medium term. If downside risks lead to a sharp reduction in growth, the authorities have policy space to act, but this needs to be done in a way that is consistent with reducing financial and corporate sector risks and achieving the desired rebalancing of the economy toward consumption and private investment. The key medium-term priorities are to deepen structural reforms to strengthen productivity growth and private investment, while accelerating rebalancing toward consumption, services, and green growth. This would require addressing market distortions and mainstreaming environmental sustainability into China's medium-term development strategy. Implementation of these priorities would boost China's long-term growth prospects; it would also help move toward a more comprehensive and lasting resolution of remaining deep-seated disagreements on global trade and investment, and public goods agenda.